Nucleoporin TPR is an integral component of the TREX-2 mRNA export pathway - Vasilisa Aksenova (Nature Portfolio, 2020)
mRNAs export from the nucleus is thought to be regulated in part by three nucleoporins that comprise the nuclear basket, but whether and how distinct basket nucleoporins interact with the RNA export machinery is unclear. Here, the authors use rapid auxin-mediated degradation of basket nucleoporins Nup153, Nup50, and Tpr, and see that Tpr interacts with the TREX-2 mRNA export complex.